The Impact of Industry 4.0 on Türkiye's Foreign Trade in Line with Sustainable Development Goals - Bozta?, Asena; Ulunç, Rabia (International Business and Accounting Research Journal, 2024)
Industry 4.0, together with the revolutionary developments in information and communication technologies, brings about radical transformations in many sectors. These transformations have significant impacts on Türkiye's foreign trade strategies and sustainable development goals. Industry 4.0 promotes economic growth through the adoption of sustainable production and consumption models and ensures more efficient use of environmental resources. While Türkiye's foreign trade is strengthened by the digital and technological innovations offered by Industry 4.0, this process also increases international competitiveness and contributes to the realisation of sustainable development goals. This study comprehensively analyses the effects of Industry 4.0 on Türkiye's foreign trade along with sustainable development goals, and examines how Türkiye has benefited from this transformation process and its effects at the international level.